A Systematic Review of Demand-Based Capacity Planning in the Emergency Department of the Hospital - Khatri, Khushboo; Prusty, Ramakanta (Journal of Neonatal Surgery, 2025)
The emergency department (ED) is an important entry point for healthcare systems that often function under strong pressure due to unpredictable patient volumes. The requested capacity plan is intended to coordinate resources with patient requirements in real time to ensure a timely, safe and effective supply. This review examines demand-based capacity planning from healthcare leaders, managers, and professionals perspective and examines strategies, challenges, tools and future directions for effective resource management in EDs. The ED is a dynamic and high-stakes environment that operates at the threshold of chaos, demanding continuous adaptability, strategic foresight, and leadership excellence. As healthcare systems confront growing patient volumes, limited resources, and unpredictable case mixes, demand-based capacity planning has emerged as a vital tool to optimize care delivery and ensure operational resilience. Healthcare managers in the ED serve as key drivers of system performance, balancing clinical urgency with resource allocation. The review highlights how senior ED leadership must engage in continuous planning, simulation, and strategic adjustment to maintain patient flow, mitigate overcrowding, and enhance care quality especially during surges in demand. Furthermore, this paper explores the intersection of people, systems, and physical environments as critical components in capacity planning. Managers must be agile in change management, aligning operational innovations with team values to embed improvements at all levels. Ultimately, the success of demand-based capacity planning hinges not only on data-driven models but also on the leadership capacity to transform challenges into coordinated responses. The findings underscore that the effectiveness of ED services is inextricably linked to the quality of its leadership and the strength of its organizational framework.